2016
DOI: 10.1111/jcpt.12447
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the intensity of lipid-lowering medications on the LDL cholesterol treatment goals of Asian patients with dyslipidaemia in primary care

Abstract: Overall, 27·6% of patients with dyslipidaemia, including 30% of the HR group, did not achieve LDL-C treatment goals, despite on LLT. Addressing their concerns and adjusting medication doses of their LLT are needed for better outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The CHILLAS trial in a Chinese ACS population has shown that doubling the statin dosage to 40 mg instead of 20 mg only resulted in an LDL-C reduction of 6.4% [ 16 ]. Other studies on adult Asian patients with dyslipidemia also have demonstrated that medium- and high-intensity statins lowered LDL-C levels by a similar proportion or similar proportions of patients who had achieved the LDL-C goals [ 17 , 18 ]. However, it is noteworthy that the LDL-C target for most dyslipidemia patients is less stringent than that for DM patients post-ACS.…”
Section: Discussionmentioning
confidence: 96%
“…The CHILLAS trial in a Chinese ACS population has shown that doubling the statin dosage to 40 mg instead of 20 mg only resulted in an LDL-C reduction of 6.4% [ 16 ]. Other studies on adult Asian patients with dyslipidemia also have demonstrated that medium- and high-intensity statins lowered LDL-C levels by a similar proportion or similar proportions of patients who had achieved the LDL-C goals [ 17 , 18 ]. However, it is noteworthy that the LDL-C target for most dyslipidemia patients is less stringent than that for DM patients post-ACS.…”
Section: Discussionmentioning
confidence: 96%
“…Angina pectoris is a major cause of disability worldwide, and angina pectoris is mainly caused by coronary artery disease or atherosclerosis [7]. Previous findings showed that there are treatment options for coronary artery disease, including medical treatment (cholesterol-lowering medications [8,9], aspirin [10], beta blockers [11], ranolazin [12], nitroglycerin [13], calcium channel blockers [14]), coronary interventions (angioplasty and coronary stent), and coronary artery grafting [15].…”
Section: Introductionmentioning
confidence: 99%